The kallikrein-kinin system in experimental Chagas disease: a paradigm to investigate the impact of inflammatory edema on GPCR-mediated pathways of host cell invasion by Trypanosoma cruzi - Scharfstein, Julio; Andrade, Daniele; Svensjö, Erik; Oliveira, Ana Carolina; Nascimento, Clarissa R. (Frontiers in Immunology, 2013)
Chronic chagasic myocarditis (CCM) depends on Trypanosoma cruzi persistence in the myocardium. Studies of the proteolytic mechanisms governing host/parasite balance in peripheral sites of T. cruzi infection revealed that tissue culture trypomastigotes (TCTs) elicit inflammatory edema and stimulate protective type-1 effector T cells through the activation of the Kallikrein-Kinin System (KKS). Molecular studies linked the proinflammatory phenotype of Dm28c TCTs to the synergistic activities of tGPI, a lipid anchor that functions as a TLR2 ligand, and cruzipain, a kinin-releasing cysteine protease. Analysis of the dynamics of inflammation revealed that TCTs activate innate sentinel cells via TLR2, releasing CXC chemokines, which in turn evoke neutrophil/CXCR2-dependent extravasation of plasma proteins, including high molecular weight kininogen (HK), in parasite-laden tissues. Further downstream, TCTs process surface bound HK, liberating lysyl-BK (LBK), which then propagates inflammatory edema via signaling of endothelial G-protein-coupled bradykinin B2 receptors (BK2R). Dm28 TCTs take advantage of the transient availability of infection-promoting peptides (e.g., bradykinin and endothelins) in inflamed tissues to invade cardiovascular cells via interdependent signaling of BKRs and endothelin receptors (ETRs). Herein we present a space-filling model whereby ceramide-enriched endocytic vesicles generated by the shingomyelinase pathway might incorporate BK2R and ETRs, which then trigger Ca2+-driven responses that optimize the housekeeping mechanism of plasma membrane repair from cell wounding. The hypothesis predicts that the NFB-inducible BKR (BK1R) may integrate the multimolecular signaling platforms forged by ceramide rafts, as the chronic myocarditis progresses. Exploited as gateways for parasite invasion, BK2R, BK1R, ETAR, ETBR and other GPCR partners may enable persistent myocardial parasitism in the edematous tissues at expense of adverse cardiac remodelling.